Directive Speech Acts Reflecting Political Power in Black Panther: Wakanda Forever (2022) - Syifa Widianisa; Deuis Sugaryamah; Erlan Aditya Ardiansyah (Universitas Cokroaminoto Palopo, 2026)
This study investigates directive speech acts in Black Panther: Wakanda Forever by examining their linguistic realization, degrees of directness, and representation of political authority. The study aims to explain how directive speech acts function not only to direct actions but also to construct political authority within cinematic discourse. This research employed a qualitative descriptive design using Searle’s (1979) speech act theory and Weber’s (1947) theory of authority. Although Weber distinguishes traditional, charismatic, and legal-rational authority, this study focuses only on legal-rational and charismatic authority because these were the only authority types identified in the selected data. The data consisted of 24 directive utterances produced by the main characters, namely Shuri, Queen Ramonda, and Namor, which were collected through observation and document analysis. The findings reveal that commands are the most dominant directive speech act, followed by warnings, requests, suggestions, and advice. In terms of linguistic realization, directive speech acts are linguistically realized through declarative (16), imperative (7), and interrogative (1) forms, with declarative forms occurring most frequently. In terms of degree of directness, indirect directives (14) occur more frequently than direct directives (10). Furthermore, the analysis shows that directive speech acts represent both legal-rational and charismatic authority. Legal-rational authority is reflected through institutional legitimacy and hierarchical control, whereas charismatic authority is constructed through persuasion, cooperation, and interpersonal influence. These findings indicate that political authority in cinematic discourse is dynamically constructed through linguistic form, communicative intention, context, and social relations rather than being determined solely by grammatical structure. This study contributes to pragmatic studies by demonstrating the relationship between directive speech acts, linguistic realization, directness, and political authority in cinematic discourse.